A dual‐band implantable antenna with wide‐band characteristics at MICS and ISM bands. Issue 12 (24th October 2018) - Basir, A.; Bouazizi, A.; Zada, M.; Iqbal, A.; Ullah, S.; Naeem, U.
Abstract: This letter presents the design of a miniaturized dual‐band spiral antenna for biomedical applications. The recommended antenna covers both the Medical Implant Communication Service MICS (402‐405 MHz) as well as the Industrial Scientific Medical ISM (2.4‐2.48 GHz) band. Different size reduction techniques have been applied to downsize the antenna and the latter achieved a compact size of 14 × 17 × 0.25 mm 3 . For validation purpose, measurements were conducted in the saline solution having properties comparable to muscles. The structure achieves very good measured peak gain values of −33 dBi and − 16 dBi at 403 MHz and 2.45 GHz, respectively. The proposed antenna has a wide‐band characteristic at both bands, which is the key for an antenna to be implanted into different tissue environments. Both the simulated and measured impedance bandwidths are sufficiently covering the intended bands. A decent agreement is observed between simulated and measured results.